PENGARUH PEDAGOGI KRITIS TERHADAP SIKAP CINTA TANAH AIR PESERTA DIDIK DALAM TANTANGAN GLOBALISASI DI KOTA BANDUNG - Dyah Nawang Wulan, - (2019)
The negative effect of globalization is the identity crisis and the fading of patriotism. In addition, forming an environmental attitude, geography learning forms the patriotism attitude of students. Critical pedagogy is forming conscientization student, to form a patriotism attitude need learning that forms an awareness. The purpose of this study is to analyze 1) teacher knowledge about critical pedagogy 2) patriotism attitude in the globalization challenges of students 3) the influence of critical pedagogy toward patriotism attitude student in globalization challenges. This study used a survey method. Data collection through questionnaires. The subjects of this study were geography teachers and students of class XI IPS in Bandung High Schools. The sample of teachers is 8 and the sample of students is 225. Data analysis techniques were using descriptive statistics and inferential statistics used Simple Linear Regression. The results of this study 1) not all teachers know the critical pedagogy; 2) the student patriotism attitude on globalization challenges in Bandung is included in the medium category; 3) there is influance of critical pedagogical to patriotism student attitude in the globalization challenges. Critical pedagogy can be used to form the patriotism student attitude.